Anticancer role of antidiabetic drug Metformin in ovarian cancer cells - Seema Patel (International Journal of Cancer Therapy and Oncology, 2016)
Purpose: Epithelial ovarian cancer is the most common ovarian cancer and has life threatening implications. Despite the progress in surgical and therapeutic strategies, resistance to chemotherapy is still a major concern. Chemotherapeutic agents cause cytotoxicity, primarily by the induction of apoptosis. The status of p53 is a key factor in determining the efficacy of apoptotic signaling. p53 is the most commonly mutated tumor suppressor gene in ovarian cancer. Metformin (an antidiabetic drug) has shown putative effects in many solid tumors. Hence we aimed to study the role of metformin in p53 mutated cancer cells. Methods: SKOV3 and OAW42 ovarian cancer cell line were used. The cancer cells were treated with metformin. MTT, Flow cytometry and Western blotting were used to characterize the effects of the different treatments. Results: Metformin treatment leads to cell cycle arrest in the G0/G1, S and G2/M phase of the cell cycle in SKOV3 and OAW42 respectively. Moreover, there was upregulation of Bax and downregulation of Bcl-2 protein and increased apoptosis in SKOV3 and OAW42 ovarian cancer cells. Conclusion: These findings support the potential of metformin to be used as chemoadjuvant and reflects its ability to sensitize cancer cells to apoptosis independent of p53 status.